2015
DOI: 10.5688/ajpe79680
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a Multi-faceted Educational Intervention to Increase Student Scholarship

Abstract: Objective. To increase the percentage of state, national, or international student presentations and publications. Design. A multi-faceted intervention to increase student scholarly output was developed that included: (1) a 120-minute lecture on publication of quality improvement or independent study research findings; (2) abstract workshops; (3) poster workshops; and (4) a reminder at an advanced pharmacy practice experience (APPE) meeting encouraging students to publish or present posters. The intervention e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…1 However, the few studies evaluating required PharmD research training that include quantitative outcomes, such as publications, presentations, or measurable change in knowledge, confidence, and interest regarding research, often note that more scholarship is needed in these areas so that colleges of pharmacy can know how many of these benefits are achievable. 4,[7][8][9] To realize these potential benefits, the University of Utah College of Pharmacy implemented required mentored student research or quality improvement projects as part of a broader curriculum revision starting with the Class of 2019. This article describes the structure of the program and evaluates the impact on and feasibility for the first graduating students to complete the program.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, the few studies evaluating required PharmD research training that include quantitative outcomes, such as publications, presentations, or measurable change in knowledge, confidence, and interest regarding research, often note that more scholarship is needed in these areas so that colleges of pharmacy can know how many of these benefits are achievable. 4,[7][8][9] To realize these potential benefits, the University of Utah College of Pharmacy implemented required mentored student research or quality improvement projects as part of a broader curriculum revision starting with the Class of 2019. This article describes the structure of the program and evaluates the impact on and feasibility for the first graduating students to complete the program.…”
Section: Introductionmentioning
confidence: 99%
“…7 Cooley et al found that the presentation/publication rate for students, including quality assurance and research projects, increased from 64% to 81% of students following an intervention. 12 Riveros et al noted that about half of studies registered in ClinicalTrials.gov were not published, 39 and Weber et al found that 55% of papers presented at a medical conference were not published five years later. 40 However, an appropriate presentation and publication rate has not been established, and, indeed, there is not agreement that extramural presentations and publications are appropriate outcomes to consider for student research.…”
Section: Discussionmentioning
confidence: 99%
“…Cooley et al demonstrated that a student survey identified only 64% of the publications and presentations that were identified using multiple other methods (eg, review of student CVs, review of posters presented at conferences). 12 The third area with risk for bias was reporting. To calculate publication and presentation rates, an accurate denominator is required that clearly denotes the number of projects that serve as the basis for calculation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations